Dinamika “Occupations” Dalam Perspektif Ibu-Ibu Yang Merawat Anak Dengan Autisme Dan Dampaknya Terhadap Kualitas Hidup (Life Quality) Sehari-Hari - Eko Sumaryanto; Gandes Mutiara Aziz (Jurnal Keterapian Fisik, 2019)
Background : As the challenges arise in raising children with autism, mothers experience changes with their occupations and also on how they define them. This later alters the overall wellbeing both psychosocially and physically as changing on health status determines the life quality. Parents, particularly mothers with autistic children may encounter dynamic to their life quality as they discover adjustment on meanings of occupations while fostering their children. Research purposes of the study are to discover and to explore the mothers interpretations on their current occupations related to their role as main caregivers of their autistic children. Methods: This is a qualitative study with phenomology approach to discover and to explore the meaning of occupations and the dynamic of perceived-life quality as the meanings of occupations might shifting along the nurturing processes. This study had selected four people as research participants. The data were then collected through in-depth interviews and followed with thematic analysis. Results: Based on the analysis process, this study highlighted three main themes as follow, the general changes in life, the values of roles, and the perceived-life quality. Mothers who foster their autistic children had reported various changes in their daily occupations and how they perceived the meanings of these occupations as the diagnoses have altered the familial hierarchy within their domestic environments; this later also has significant impacts on their perceived-quality of life while fulfilling their role as the main house keepers. Thus, all these changes enforce the mothers to always strive on their best as this effort will eventually deliver positive meanings, such as self-confidence, greater responsibilities related to the roles as a mother and the possitive supports received from their support systems. Conclusion: The respondents reported the overwhelming perceived-satisfactions when talking about their quality of life. This is the result from personal beliefs over the ability to devote their life for the children and the family despite the perceptions that they are still unable to enjoy their general life ideally.